Probiotics and Prebiotics as Functional Foods: State of the Art - Khaneghah, Amin M.; Fakhri, Yadolah (Current Nutrition & Food Science, 2019)
Foods, besides their nutritional value, are used to be as a tool in maintaining of physical and mental well-being and prevent disease. Based on the definition of Functional foods as foods, which may offer health benefits beyond basic nutrition, functional foods, are categorized as foods, not medicine. Among the last decades, the growing market for functional foods, representing both opportunities and challenges to food producers as well academic sections to cover such demand and furthermore conquer the acceptance of consumer. In this article, an overview regarding the probiotics as well as prebiotics as outstanding components of functional foods, compatibility and their use in food products have been reviewed.
Keywords: Consumer